Exploring the Inner Voices: An Interpretative Phenomenological Analysis of Irrational Beliefs among Individuals with Prescription Drug Addiction - Selvi Shofiatus Sholihah Nurfazrin; Gian Sugiana Sugara; Anandha Putri Rahimsyah (Edupotensia, 2025)
Prescription drug abuse is a serious issue in the field of mental health, impacting various aspects of an individual's life, including psychological dimensions such as irrational beliefs. This study aims to explore the manifestation of irrational beliefs in individuals with prescription drug addiction. A qualitative approach was employed using a case study design. The research involved two participants who had experienced prescription drug addiction and undergone a rehabilitation process. Data were collected through in-depth interviews, observation, and documentation, and then analyzed using thematic analysis. The findings revealed that the participants held irrational beliefs in the form of negative self-perceptions, a belief that drugs are the solution to all problems, and intolerance to emotional discomfort. These beliefs were shaped by past experiences, environmental influences, and a lack of emotional support. The findings emphasize the importance of cognitive interventions such as Cognitive Behavioral Therapy (CBT) in addressing irrational beliefs as part of the recovery process from addiction.